Soil properties change, and arbuscular mycorrhizal fungi associated with plants growing on the post-gold mining land of Bombana, Indonesia - Tuheteru, Edy Jamal; Tuheteru, Faisal Danu; Hartami, Pantjanita Novi; Burhannudinnur, Muhammad; Prakoso, Suryo; Husna, H; Albasri, A; Asraria, Dian (Journal of Degraded and Mining Lands Management, 2023)
This study aimed to investigate the effect of gold mining on soil properties. Soil samples were taken from the post-gold mining land, the property of PT Panca Logam Nusantara and PT Alam Buana Indonesia, and a nearby natural forest in Bombana, Southeast Sulawesi Province. The next step focused on specifying soil pH, total nitrogen (TN) and carbon (TC) concentration, C/N ratio, available phosphorus (P) concentration, cation exchange capacity (CEC), and exchangeable K, Na, Mg, Ca, Fe, Mn, Cd and Pb concentration, texture and spore amount, AMF resource and AMF colonization. The result shows that the pH in post-gold mining soil was higher than that in natural forest soil. Meanwhile, TN, TC, available P, and CEC of post-gold mining soil got lower compared with these of natural forest soil. The texture in the post-mining soil was clay loam, while that in natural forest soil was clay. Total of 10 AMF species belonging to five genera and three families were found in a post-gold mining area. Soil pH, CEC, soil texture, Mn, and total Fe had a negative relation with AMF colonization and spore count, while organic C, total N, C/N ratio, P2O5 and silt had a positive relation. Sand was proven to have a strong and positive correlation with the amount of AMF species. Adding organic matter and fertilization as well as applying mycorrhizal biofertilizers, were urgently required to support the effort in restoring post-gold mining soil.